Effects of different polymers on mechanical properties of bituminous binders and hot mixtures - Alatas, Taner; Yilmaz, Mesude (Elsevier Sci Ltd, 2013)
In this study, rheological and mechanical properties of bituminous binders and hot mixtures modified by different polymeric additives, Kraton D1101, Kraton MD243 and Evatane (R) 2805, were examined. In all samples, the amount of the polymeric additive was kept constant at 4 wt.% of the bituminous binder. The experiments showed that with the addition of the polymer to binder, Marshall stability, retained Marshall stability, indirect tensile strength, tensile strength ratio, stiffness and fatigue life values of the bituminous hot mixtures increased. The effect of the EVA on stiffness modulus and fatigue life was found to be notable. When toughness index values were compared, it was detected that mixtures with SBS-Kraton MD243 demonstrated the highest elasticity, while those with EVA-Evatane (R) 2805 showed the least. The rheological experiments on the binders figured out that by the use of MD243, a new type of styrene-butadiene-styrene additive, low viscosity values could be obtained. This implies that if MD243 is utilized to bituminous mixtures, an effect on bituminous mixtures similar to that created by D1101 addition could be obtained by consuming less amount of energy. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Modification; Hot mix asphalt; SBS; EVA; Superpave